2006
DOI: 10.1007/s11420-006-9006-3
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Method for the Quantitative Evaluation of Lumbar Spinal Stenosis

Abstract: Study design: A retrospective study of computed tomography (CT) myelographic images in patients with degenerative lumbar spinal stenosis (LSS). Objectives: To introduce a new technique for the quantitative evaluation of LSS. Background: Advances in hardware and software technology now permit inexpensive digitalization of radiological images, and enable methodologies for quantifying space available for neural elements in spinal canal. However, a valid method with quantitative evaluation of spinal stenosis in li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 36 publications
(50 reference statements)
0
21
0
1
Order By: Relevance
“…Zheng et al [67] have revealed that the AP diameter of the spinal canal and the AP diameter of the vertebral body do not provide any evaluation in DLSS, contrary to the congenital type. Singh et al [9] characterized congenital stenosis through MR imaging and stated that the AP diameter of the spinal canal, pedicle length and vertebral body width were significantly smaller in the stenosis group, whereas no difference was found in the vertebral body AP diameter and body height, compared to the control.…”
Section: Discussionmentioning
confidence: 99%
“…Zheng et al [67] have revealed that the AP diameter of the spinal canal and the AP diameter of the vertebral body do not provide any evaluation in DLSS, contrary to the congenital type. Singh et al [9] characterized congenital stenosis through MR imaging and stated that the AP diameter of the spinal canal, pedicle length and vertebral body width were significantly smaller in the stenosis group, whereas no difference was found in the vertebral body AP diameter and body height, compared to the control.…”
Section: Discussionmentioning
confidence: 99%
“…First, related to the methodology, since the researchers measured stenosis via the anteroposterior diameter in the MRI and not via the dural sac CSA. The CSA measurements of the dural sac have previously been emphasised as the best option for studying spinal canal stenosis 18,19,20 . CSA measurements via MRI yield a high interobserver reproducibility 21 .…”
Section: Discussionmentioning
confidence: 99%
“…The symptoms of spinal stenosis alone can be disabling, leading to physical deconditioning, loss of lean body mass, decreased cardiac and pulmonary functions, and depression. 15 Surgeons evaluating these patients must thus weigh the potential benefits of surgery against substantial medical comorbidities.…”
Section: Discussionmentioning
confidence: 99%
“…Improvements in ambulation were also demonstrated at rates similar to those in younger patients. 9,7,13,15 The increased risks of surgery must be discussed with the patient in the context of predicted functional gains. The strategies used in an attempt to minimize perioperative complications in all cases in which substantial blood loss is expected accurate accounts of intraoperative blood loss should be done and replaced.…”
Section: Discussionmentioning
confidence: 99%